2023
DOI: 10.18632/oncotarget.28457
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the prevalence of pathogenic variants in Saudi Arabian patients with familial cancer using a multigene next generation sequencing panel

Abstract: Family history is an important factor in determining hereditary cancer risk for many cancer types. The emergence of next-generation sequencing (NGS) has expedited the discovery of many hereditary cancer susceptibility genes and the development of rapid, affordable testing kits. Here, a 30-gene targeted NGS panel for hereditary cancer risk assessment was tested and validated in a Saudi Arabian population. A total of 310 subjects were screened, including 57 non-cancer patients, 110 index patients with cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…This study identified 13 common variants, two of which were thought to be potential pathogenic variants. The APC c.3920T>A variant is associated with Lynch syndrome and the TP53 c.868C>T variant is associated with colon polyposis [ 16 ]. A previous study also employed NGS, Sanger sequencing, and Multiplex Ligation-dependent Probe Amplification to identify mismatch repair gene variants in individuals with Lynch syndrome.…”
Section: Recent Screening Projects In Saudi Arabiamentioning
confidence: 99%
See 1 more Smart Citation
“…This study identified 13 common variants, two of which were thought to be potential pathogenic variants. The APC c.3920T>A variant is associated with Lynch syndrome and the TP53 c.868C>T variant is associated with colon polyposis [ 16 ]. A previous study also employed NGS, Sanger sequencing, and Multiplex Ligation-dependent Probe Amplification to identify mismatch repair gene variants in individuals with Lynch syndrome.…”
Section: Recent Screening Projects In Saudi Arabiamentioning
confidence: 99%
“…Multiple studies have reported fear and embarrassment as barriers among populations [ 19 , 26 , 27 ]. In a cross-sectional study that focused on the preferred screening methods among the population, 50% attributed their choice to how the test was performed, choosing fecal immunochemical test (FIT) as the most preferred screening method for 41.7% of the population [ 16 ]. Other barriers include a lack of knowledge about screening, as stated in a previous study [ 28 ].…”
Section: Patients' Barriersmentioning
confidence: 99%
“…It has been suggested that some pathogenic variants linked with cancer which are common in the European population show lower association with cancer in other ethnic groups such as people of Arab descent [74]. In a previous study in Saudi Arabian breast cancer patients, 37 potential variants in 25 breast cancer risk associated genes other than BRCA1/2 were identified including variants in MLH1, MLH3 genes [75].…”
Section: Plos Onementioning
confidence: 99%
“…To date, 604 different PALB2 variants have been identified; only 140 variants are considered pathogenic, while ~400 have unclear significance ( 4 ). The presence of a heterozygous germline mutation in PALB2 has been linked to the emergence of breast, pancreatic and ovarian cancer ( 5 ). A study in Saudi Arabia linked association of PALB2 pathological variants (PVs) with familial cancer in patients with breast and colon cancer and relatives with a family history of cancer ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a heterozygous germline mutation in PALB2 has been linked to the emergence of breast, pancreatic and ovarian cancer ( 5 ). A study in Saudi Arabia linked association of PALB2 pathological variants (PVs) with familial cancer in patients with breast and colon cancer and relatives with a family history of cancer ( 5 ). Similarly, an international study ( 6 ) analysed >500 families from 21 countries with PALB2 PVs and reported the link between PALB2 PVs with breast, ovarian and pancreatic cancer; however, prostate and colorectal cancer were independent of PALB2 .…”
Section: Introductionmentioning
confidence: 99%